The Role of Kedamangan in Imposing the Customary Sanction Singer Sule Kasalan Luang in Cases of Dissemination of False Information in Kedamangan Jekan Raya, Palangkaraya City - Valentia, Ennisa; Farina, Thea; Januardy, Ivans (Dinasti Research, 2025)
This study explores the role of the Kedamangan institution in adjudicating cases involving the dissemination of false information within the indigenous Dayak Ngaju community in Jekan Raya, Palangka Raya City. Anchored in Article 18B(2) of the 1945 Constitution of Indonesia and regional customary laws such as the Tumbang Anoi Agreement of 1894 and Central Kalimantan Regional Regulation No. 1 of 2010, the research examines how the traditional leader (Damang) exercises judicial authority in imposing the Singer Sule Kasalan Luang sanction—a customary fine imposed on individuals who spread defamatory or harmful false news. Utilizing an empirical juridical method, the study combines normative legal analysis with qualitative field data, including interviews with former Damang Kardinal Tarung. Findings demonstrate that the Damang holds recognized authority to resolve disputes and impose sanctions through culturally embedded mechanisms aimed at restoring communal harmony and deterring future offenses. The research also establishes that decisions rendered by the Damang, when accepted by both parties, possess final and binding legal force (BHT) under customary law and may be enforced without recourse to the state judiciary. However, dissatisfied parties retain access to formal legal institutions, reflecting a pluralistic legal framework that accommodates both customary and positive law. This study underscores the relevance of indigenous legal practices in addressing contemporary issues such as misinformation, and highlights the need for further research into the comparative effectiveness and legal recognition of customary justice across diverse regions.